2006
DOI: 10.1086/500560
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Kaposi Sarcoma–Associated Herpesvirus (KSHV) in KSHV‐Associated Diseases

Abstract: Numbers of viral copies and of virus-positive cells vary among KSHV-associated diseases, which suggests different mechanisms of viral pathogenesis. The combination of real-time PCR and computerized-image analysis provides a useful tool for the assessment of the number of viral copies in KSHV-associated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 35 publications
4
41
0
1
Order By: Relevance
“…The relationship between surface molecule expression and increasing numbers of LANA dots suggested that KSHV-induced modulation of immune synapse components was dependent on intracellular viral copy number. Moreover, these data also indicated that downregulation was evident even with the lower levels of viral load reminiscent of those in the infected cells of KS (2). Knockdown of MIR2 results in loss of downregulation following de novo KSHV infection.…”
Section: Mir2 Transduction Mirrors Downregulation Observed During Thementioning
confidence: 67%
See 1 more Smart Citation
“…The relationship between surface molecule expression and increasing numbers of LANA dots suggested that KSHV-induced modulation of immune synapse components was dependent on intracellular viral copy number. Moreover, these data also indicated that downregulation was evident even with the lower levels of viral load reminiscent of those in the infected cells of KS (2). Knockdown of MIR2 results in loss of downregulation following de novo KSHV infection.…”
Section: Mir2 Transduction Mirrors Downregulation Observed During Thementioning
confidence: 67%
“…While the degree of KSHV infection positively corresponded with the amount of MIR2 expressed in the population, we wanted to evaluate the role of KSHV-episome dosage on downregulation in individual cells to ascertain whether this effect could occur in cells infected with minimal numbers of virions, as would likely occur in vivo (2). Although it seemed clear that the degree of downregulation of ICAM-1 and MHC-I paralleled the level of input virus added to a population of target cells (Fig.…”
Section: Mir2 Transduction Mirrors Downregulation Observed During Thementioning
confidence: 99%
“…The reaction mixtures were incubated at 95°C for 5 min, followed by 40 cycles of 95°C for 15 s and 60°C for 1 min. The JCV DNA copy numbers per cell were calculated by dividing the JCV copy numbers by half of the beta-actin copy numbers, because each cell had two copies of the gene in two alleles (50).…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular viral load varies by disease type; it is high, for example, in primary effusion lymphomas and low in infected endothelial (spindle) cells in Kaposi's sarcoma lesions (1).…”
mentioning
confidence: 99%